Examining The Relationship between Social Comparison on Self-Acceptance among Senior High School Students in Sleman Regency - Marissa, Siti; Wangid, Muhammad Nur (FKIP - Universitas Riau, 2026)
The study aims to determine the relationship between social comparison and self-acceptance. This study employed a correlational research design. The population consisted of 9.828 students from seventeen public senior high schools in Sleman Regency. A sample of 367 students was selected using a two stage sampling technique. Data were collected using two psychological instruments: the Iowa-Netherlands Comparison Orientation Measure (INCOM), and Berger’s Self-Acceptance Scale. Instrument validity was determined through expert judgment, while reliability testing using Cronbach’s Alpha yielded coefficients of 0.788 for social comparison, and 0.937 for self-acceptance. Data analysis was conducted using descriptive statistics, and simple linear regression, with the assistance of SPSS 25 for Windows. There is a negative and significant relationship between social comparison and self-acceptance in public high school students in Sleman Regency, with Sig=0.000 (Sig<0.005) and a correlation value of -0.403. This means that the higher the social comparison, the lower the self-acceptance. Social comparison provides an effective contribution to self-acceptance of 16.3%.